2016
DOI: 10.5194/esurf-4-471-2016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Holocene vegetation changes on topography and erosion rates: a case study at Walnut Gulch Experimental Watershed, Arizona

Abstract: Abstract. Quantifying how landscapes have responded and will respond to vegetation changes is an essential goal of geomorphology. The Walnut Gulch Experimental Watershed (WGEW) offers a unique opportunity to quantify the impact of vegetation changes on landscape evolution over geologic timescales. The WGEW is dominated by grasslands at high elevations and shrublands at low elevations. Paleovegetation data suggest that portions of WGEW higher than approximately 1430 m a.s.l. have been grasslands and/or woodland… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…For example, we assume a linear relationship between A and x t . Alternative model formulations are possible, such as that of a power law relationship, where A = bx y t [Pelletier et al, 2016]. However, using this alternative power law relationship predicts the same relationship between D d and E as that of our simpler scenario (see supporting information).…”
Section: Theoretical Backgroundmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, we assume a linear relationship between A and x t . Alternative model formulations are possible, such as that of a power law relationship, where A = bx y t [Pelletier et al, 2016]. However, using this alternative power law relationship predicts the same relationship between D d and E as that of our simpler scenario (see supporting information).…”
Section: Theoretical Backgroundmentioning
confidence: 80%
“…Furthermore, our model scenario neglects colluvial infilling of the valley head (equation (4)). Pelletier et al [2016] present a transport-limited model for predicting drainage density, calibrated for the Walnut Gulch Experimental Watershed, Arizona, where they assume that the valley head occurs where the fluvial erosion rate is greater than the colluvial deposition rate by an amount equal to the net erosion rate E. In the model outlined above, we follow a similar approach to Tucker and Bras [1998] by assuming that the valley head occurs where the fluvial erosion rate is greater than colluvial erosion. Including colluvial deposition at the valley head in our analytical model may lead to decreased absolute values of drainage density.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This provides an opportunity to hypothesize about the impact of changing ecological or climatological conditions. For example, imagine a substantial shift in climate which drives an ecologic change from a grassland to a shrubland (Pelletier et al, ). Under these new conditions, long‐distance transport events may become more common as there are fewer vegetative anchors for the soil which reflects an increase in E .…”
Section: Discussionmentioning
confidence: 99%
“…This type of analysis is similar to efforts that explore what values of the diffusivity‐like rate constant D might take on in different settings. It is largely suggested that it varies as a function of climate and ecology (Hughes et al, ; Istanbulluoglu & Bras, ; Pelletier et al, ; Tucker & Bras, ). However, this problem is a complex one that involves the specifics of ecology, geology, and climatology.…”
Section: Discussionmentioning
confidence: 99%
“…This is part of a larger pattern of increased upwelling and reduction of the extent of the tropical warm-water pool toward the end of the Pliocene [Brierley et al, 2009] associated with intensification of Hadley circulation [Fedorov et al, 2013]. Amplified climate variation after 3 Ma [Zachos et al, 2001] may especially enhance erosion and sediment export from semiarid shrubland regions, including the upper elevations of catchments draining into the FCVB, due to cyclic changes of vegetation cover [Bull, 1991;Pelletier, 2014;Pelletier et al, 2016;Dosseto and Schaller, 2016]. Alternatively, tectonic controls may have driven the progradation.…”
Section: Testing Drivers Of Sediment Progradation With 10 Bementioning
confidence: 99%